Autonomic Dysfunction Predicts Clinical Outcomes After Acute Ischemic Stroke: A Prospective Observational Study. Issue 1 (January 2018) - Xiong, Li; Tian, Ge; Leung, Howan; Soo, Yannie O.Y.; Chen, Xiangyan; Ip, Vincent H.L.; Mok, Vincent C.T.; Chu, Winnie C.W.; Wong, Ka Sing; Leung, Thomas W.H.
Abstract : Background and Purpose—: Central autonomic dysfunction increases stroke morbidity and mortality. We aimed to investigate whether poststroke autonomic dysfunction graded by Ewing battery can predict clinical outcome. Methods—: In this prospective observational study, we assessed autonomic function of ischemic stroke patients within 7 days from symptom onset by Ewing battery. On the basis of the magnitude of autonomic dysfunction, we stratified patients into significant (definite, severe, or atypical) or minor (normal or early) autonomic function impairment groups and correlated the impairment with the 3-month modified Rankin Scale score (good outcome: modified Rankin Scale score 0≈2; poor outcome: modified Rankin Scale score 3≈6). Results—: Among the 150 patients enrolled (mean age, 66.4±9.9 years; 70.7% males), minor autonomic dysfunction was identified in 36 patients (24.0%), and significant autonomic dysfunction was identified in 114 patients (76.0%) based on Ewing battery. In 3 months, a poor functional outcome was found in 32.5% of significant group patients compared with 13.9% in the minor group ( P =0.031). Crude odds ratios of the magnitude of autonomic dysfunction and 3-month unfavorable functional outcome after acute ischemic stroke were 2.979 (95% confidence interval, 1.071–8.284; P =0.036). After adjusting for confounding variables with statistical significance between the 2 functional outcome subgroups identified in univariate analysis (including sex and National Institutes of Health Stroke Scale score on admission), the magnitude of autonomic dysfunction still independently predicted an unfavorable outcome, with an odds ratio of 3.263 (95% confidence interval, 1.141–9.335; P =0.027). Conclusions—: Autonomic dysfunction gauged by Ewing battery predicts poor functional outcome after acute ischemic stroke. Abstract : Supplemental Digital Content is available in the text.